Larval morphology of Amphiops mater mater Sharp (Coleoptera: Hydrophilidae: Chaetarthriini) - Minoshima, Yûsuke; Hayashi, Masakazu (Zootaxa, 2012)
The larval morphology of Amphiops mater mater Sharp, 1873 is described, including chaetotaxy and morphological trans-formation between instars. Among genera of the family Hydrophilidae, the larvae of Amphiops Erichson, 1843 may bedistinguished by the following combination of characters: coronal line present; clypeolabrum almost symmetrical; man-dibles symmetrical and with three inner teeth; dorsal surface of palpomere 1 completely sclerotized; mentum with stronglyprojecting and sharply pointed anterior corners; ligula absent; spiracular atrium well developed. Several primary sensillaare absent from all instars of A. mater mater, in contrast to the stable chaetotaxy in the majority of Hydrophilidae species studied in detail to date.